Outpatient care for adolescents’ and young adults’ mental health: promoting self- and others’ understanding through a metacognitive interpersonal therapy-informed psychological intervention - Marconi, Elisa; Monti, Laura; Fredda, Giulia; Kotzalidis, Georgios D.; Janiri, Delfina; Zani, Valentina; Vitaletti, Debora; Simone, Maria Velia; Piciollo, Simone; Moriconi, Federica; Di Pietro, Emanuela; Popolo, Raffaele; et al. (Frontiers in Psychiatry, 2023)
Psychiatric disorders and symptoms in adolescents and young adults are a rapidly growing phenomenon, especially after the COVID-19 pandemic. In recent years, there have been many admissions to neuropsychiatry and child psychiatry services, leading to difficulties in the management of beds and hospital admissions. Recent studies have highlighted the role of impaired metacognition skills in the development of early psychological distress. In fact, in the adolescent and young adult psychiatric population there is often an impairment in the ability to reflect on one's own and others' mental states. In 2020, the Psychiatry service of the Fondazione Policlinico Universitario Agostino Gemelli IRCCS opened an outpatient service dedicated to adolescents and young adults, in which medical and pharmacological management were complemented by psychotherapy interventions on an outpatient basis. Among the proposed psychotherapeutic interventions, given the above-mentioned literature evidence and the demonstration of the model's effectiveness in adolescents, we proposed Metacognitive Interpersonal Therapy-informed psychotherapy for adolescents and young adults seeking psychological help. The present study compared the efficacy and feasibility of this model with psychotherapy-as-usual in an outpatient setting. We found positive results for this psychotherapy in patients with various mental disorders, with improvement on all psychometric assessments.